Analisis Tingkat Kesehatan Bank pada PT. bank Permata, Tbk. Cabang Padang - Kemala, Sri (Jurnal Ekonomi, 2012)
Banking industry has the primary function is to collect and distribute funds third party in order to improve societies welfare. To perform these functions, the Bank it self should be at the level of good health of bank financial. PT. Bank Permata is research object that publicated financial report during 2008. CAMEL method are used to identify PT. Bank Permata, Tbk will be categorized at the level of good health of bank financial. Assessment of the ratio of capital with a weight of 25%, get the result that the bank is considered healthy, in terms of assets with a 30% weighting also produces a predicate that the bank is healthy as well as assessment of bank earnings (profitability) result obtained that bank soundness is very good. It's just in terms of liquidity (weighting 10%), health of bank s are in a healthy position, due to the value of loans greater than the funds received by the bank. It is anticipated that in the absence of financing during 2008 to minimize the risk of decline in bank. From these results it is recommended that banks take action to improve liquiduty. Also expand market share, increase promotion and further empower wxisting human resources by increasing motivation to what the objective are achieve.